Enhancing Teaching Capability Through Thailand’s Teacher TV Program - Rapin Chayvimol (Bandar Lampung University (UBL), 2014)
This paper aims to present and discuss on the implementation of the TeacherTelevision (TV) Program, one of important strategic approaches in developing teaching capability of approximate 500,000 Thai teachers during 2010 - 2012. It is deemed as a highly impact teacher development innovation in the Thai educational context. The study reveals that the Program significantly assists the teachers to enhance their motivation in self-directed learning and to inspire their creativity in teaching design that leads to any classroom innovations. In this paper, an evolution of the Thai Teacher TV Program and its objectives are firstly introduced. Then, some crucial empirical data collected during the implementation period are presented for exhibiting the impact of the Program on the teachers. Last, key success factors, barriers,managerial recommendations, and a strategic framework for the policy makers in any other educational contexts arediscussed and proposed.